2014
DOI: 10.1001/jamaneurol.2014.2124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statin Use During Hospitalization for Intracerebral Hemorrhage on Mortality and Discharge Disposition

Abstract: IMPORTANCE Statin use during hospitalization is associated with improved survival and a better discharge disposition among patients with ischemic stroke. It is unclear whether inpatient statin use has a similar effect among patients with intracerebral hemorrhage (ICH). OBJECTIVE To determine whether inpatient statin use in ICH is associated with improved outcomes and whether the cessation of statin use is associated with worsened outcomes. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort study of 3481 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Exposure to statins in the acute phase of experimental stroke appears to promote angiogenesis and synaptogenesis,15 and additional pleiotropic statin effects such as vasodilatory and antithrombotic properties have been reported 16. These experimental observations are supported by clinical findings of improved outcomes with acute statin use in myocardial infarction,17, 18, 19 stroke,3, 4, 20, 21 and major vascular surgery 22, 23…”
Section: Discussionmentioning
confidence: 86%
“…Exposure to statins in the acute phase of experimental stroke appears to promote angiogenesis and synaptogenesis,15 and additional pleiotropic statin effects such as vasodilatory and antithrombotic properties have been reported 16. These experimental observations are supported by clinical findings of improved outcomes with acute statin use in myocardial infarction,17, 18, 19 stroke,3, 4, 20, 21 and major vascular surgery 22, 23…”
Section: Discussionmentioning
confidence: 86%
“…Evidence that supports the use of this approach comes from retrospective studies that showed statin use to decrease PHO and improve outcomes of ICH. 81,82 Several studies have tested other approaches to reducing brain swelling.…”
Section: Interventions In Ischaemic Strokementioning
confidence: 99%
“…Similarly, discontinuation of statins within 24 h after an ischemic stroke in a randomized setting has been shown to increase infarct size, the rates of early neurologic deterioration, and to worsen functional outcome after 3 months [62]. In a retrospective cohort study of 3481 patients with ICH admitted to one of 20 hospitals in a large integrated health care delivery system over a 10-year period, continued statin use as an inpatient was associated with improved outcomes after ICH, while the cessation of statin use was associated with worsened outcomes after ICH [63]. Analysis of 2466 consecutive patients with ICH from the Registry of the Canadian Stroke Network enrolled between 2003 and 2008 showed that discontinuation of statins was related to poor outcome even after adjustment for baseline stroke severity, but this association was no longer significant after excluding patients treated palliatively [64••].…”
Section: Potential Effects Of Statins On Outcomes After Intracerebralmentioning
confidence: 99%